Thermal and morphological changes of the Volcán de Colima lava dome 2013 – 2016 - Tonato Ñacato, Andrea Belen (2020)
Volcán de Colima is one of the most active volcanoes in North America, belonging to the western sector of the Trans-Mexican Volcanic Belt. The historical eruptive activity of Colima has been characterized by a complex succession of effusive lava-dome and/or lava flow eruptions with associated block and ash flows, and explosive eruptions of varying magnitude that have produced numerous and diverse types of pyroclastic flows and tephra falls. This thesis project analyses aerial photographs and thermal images of lava domes at Volcán de Colima from 2013 to 2016 along with a study of effusion rates for a lava dome growth in 2016. Based on the morphological changes, we defined four different phases of effusive and explosive activity of the volcano during the whole period 2013-2016. It includes phases of growth, collapse and destruction of a lava dome accompanied by changes in growth processes, temperatures, and lava textures. Thermal data showed that during the period 2013-2016, the maximum observed temperatures vary from 150ºC to 500ºC. The highest temperature was recorded during the last stage of the 2016 lava dome growth, on 4th of October. Finally, effusion rates calculated for the 2016 lava dome growth indicate a maximum value of ~3.08×104 m3days-1. Growth of the 2016 lava dome was divided into four stages depending on the effusion rate, temperature, type of extruded material, and process of growth. Our results provide important information on the underlying processes of magma movement and emplacement at shallow levels, as well as an assessment of risk and hazard.